The role of sports marketing in achieving the competitive superiority of the organization: a case study in a sample of the Iraqi Premier League clubs - Al-Faraji, Hareth Muthanna Mahmoud; JathirAl-Rabaiwi, Saadoun Hammoud (Journal of Economics and Administrative Sciences, 2021)
The organization of sporting activities at the local and international levels requires a lot of money, which has increased interest in marketing in the sports field, as it is one of the modern topics that represent the basic knowledge needed by the sports marketer and which represents one of the basic concepts to enhance the benefits and returns of sports clubs. The research problem was the weak awareness of the members of the administrative body of Iraqi sports clubs of the role of sports marketing in the dimensions of competitive superiority and not exploiting them in the optimal way that enables clubs to achieve competitive superiority. The research aims to know the role of sports marketing in competitive superiority in the Iraqi Premier League clubs. In order to reach this goal, two main research hypotheses were formulated that stipulated the first hypothesis (there is a correlation relationship of significant significance between sports marketing and competitive superiority ) What is the second hypothesis stipulated (there is a significant effect correlation between sports marketing and competitive excellence) that was subject to statistical tests and was targeted The current research is the sports sector, and the research community was represented by members of the administrative committee of the Iraqi Premier League clubs in Baghdad. It has reached (75) members. As for the method of data collection, it was done using a questionnaire and personal interviews. The statistical software Spss-v.23 was used to analyze the data. A set of statistical methods were also used, such as the mean, standard deviation, the coefficient of variation, the correlation coefficient of Spearman, and the Alpha Cronbach coefficient. The most prominent findings of the researcher were the existence of a direct correlation relationship for sports marketing in competitive superiority, and sports marketing has a positive impact on competitive superiority. As for the most prominent recommendations reached by the researcher, it is necessary for Iraqi clubs to invest in the positive relationship between sports marketing and competitive superiority in order to increase profits and provide a source of self-financing for the club